SOSIALISASI PEMANFAATAN GOOGLE PLAY BOOK UNTUK MENINGKATKAN LITERASI DIGITAL SISWA DI SMP NEGERI 4 BAUBAU - Husniah, Wa Ode; Safaria, Ria; Zulhija, Alan; Ramadan, Rahmat (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Digital literacy is an essential skill for students in the digital age. Google Play Book, as a digital book platform, offers interactive features such as text search, digital notes, and audiobooks, which can improve literacy. This service activity aims to introduce Google Play Book to seventh grade students of SMP Negeri 4 Baubau through theory and practice-based socialization. As a result, students were able to operate the application, including searching for books and utilizing its features. They also showed an increased interest in reading and awareness of the importance of digital sources as a complement to printed books. Although there are drawbacks, such as dependence on technology, the benefits in expanding access to learning and encouraging independent learning are significant. This activity is expected to be the first step in building a culture of digital literacy in schools and encouraging the wise use of technology for education. Thus, students can be better prepared to face the challenges of learning in the digital world.